Simultaneously identifying displacement and strain flexibility using long-gauge fiber optic sensors. (1st January 2019) - Li, Panjie; Zhang, Zhennan; Zhang, Jian
Highlights: The impacting test is performed on the structure to extract the exact FRFs. Strain flexibility identification based on system matrix A, B, C, D of the identified state-space models. Simultaneously identifying displacement and strain flexibility matrix based on long-gauge strain responses. Abstract: The method of simultaneously identifying displacement and strain flexibility matrices of the structure is proposed by performing the multiple reference impact test and using long-gauge (LG) fiber optic sensors. This method has the following promising features: (1) The impact test is performed in which not only structure responses but also the input force are measured, which ensures the consistency between the identified Frequency Response Function (FRF) and the analytical one, thus it has the advantage of identifying structural flexibility. In contrast, the ambient vibration test cannot output FRF magnitudes. (2) The long-gauge fiber optic sensors are used to measure structure strain responses, which has the merit of reflecting both the macro and micro characteristics of a structure. Both strain and displacement flexibility are identified simultaneously by establishing the relation between LG strain and displacement through an improved conjugate beam method. (3) The subspace identification method in the time domain is developed for structural flexibility identification. It has the merit to deal with the test data with multi-reference multi-peak impacting forces which can better excite the dynamic characteristics of the structure, while traditional frequency domain methods generally are difficult to do that due to the leakage problem. Numerical and experimental examples have been studied to verify the validity and demonstrate the promising features of the proposed method.